2020
DOI: 10.1111/acel.13262
|View full text |Cite
|
Sign up to set email alerts
|

How age and infection history shape the antigen‐specific CD8+ T‐cell repertoire: Implications for vaccination strategies in older adults

Abstract: Cytotoxic CD8 + T cells are important in the clearance of virus-infected cells and are therefore of interest for the development of vaccination strategies against infectious diseases. An important correlate of protection against infectious diseases is the recruitment of T cells carrying high-affinity antigen-specific T-cell receptors (TCRs) (Tscharke et al., 2015). The diversity of the recruited T-cell repertoire is also directly linked to disease outcome (Price et al., 2004, 2009), and narrow T-cell repertoir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 128 publications
(215 reference statements)
0
19
0
Order By: Relevance
“…Altogether, the available evidence suggests that both T cellintrinsic and T cell-extrinsic factors contribute to a reduction in TCR diversity (particularly pronounced in the CD8 + T effector memory CD45RA + (T EMRA ) subset) that compromises immune function and/or causes the disproportionate expansion of T cells specific for autoantigens or antigens encoded by persistent viruses (such as CMV and Epstein-Barr virus). This reduction in TCR diversity has been observed both in longitudinal and cross-sectional population studies 88 .…”
Section: Reduction Of Tcr Repertoirementioning
confidence: 60%
“…Altogether, the available evidence suggests that both T cellintrinsic and T cell-extrinsic factors contribute to a reduction in TCR diversity (particularly pronounced in the CD8 + T effector memory CD45RA + (T EMRA ) subset) that compromises immune function and/or causes the disproportionate expansion of T cells specific for autoantigens or antigens encoded by persistent viruses (such as CMV and Epstein-Barr virus). This reduction in TCR diversity has been observed both in longitudinal and cross-sectional population studies 88 .…”
Section: Reduction Of Tcr Repertoirementioning
confidence: 60%
“…However, the recent finding that only a very small percentage of individuals seroconvert for CMV at later age (Samson et al, 2020 ), as well as the finding that more than 90% of the population is infected with EBV during adolescence (Balfour et al, 2013 ; Winter et al, 2020 ), makes this explanation unlikely. In our view, a more likely explanation for the reduced diversity in the antigen-specific T-cell repertoire of older individuals would be that older individuals have been infected for a longer time, and have lost more T-cell clones over time, for example due to exhaustion after restimulation (Lanfermeijer et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, several cross-sectional studies into the CMV and EBV-specific T-cell repertoires reported similar Vβ-skewing in young and older adults, and even identical TCR sequences between individuals of different age groups (Khan et al, 2002 ; Schwanninger et al, 2008 ; Cardenas Sierra et al, 2014 ). Although these studies have led to the view that antigen-specific T-cell repertoires are rather stable with age, it remains unknown, if the diversity of antigen-specific T-cell repertoires is maintained (Lanfermeijer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That cells age is irrefutable ( 36 – 38 ). For instance, cellular aging has implications in cancer ( 37 41 ), and vaccination of the elderly is affected by the poor responsiveness of their aged T cells ( 40 47 ). Yet, due consideration has not been given to the aging of cells in models of memory T-cell homeostasis.…”
Section: Introductionmentioning
confidence: 99%